2018
DOI: 10.1016/j.jconrel.2018.08.019
|View full text |Cite
|
Sign up to set email alerts
|

Intradiscal delivery of celecoxib-loaded microspheres restores intervertebral disc integrity in a preclinical canine model

Abstract: Low back pain, related to degeneration of the intervertebral disc (IVD), affects millions of people worldwide. Clinical studies using oral cyclooxygenase-2 (COX-2) inhibitors have shown beneficial effects, although side-effects were reported. Therefore, intradiscal delivery of nonsteroidal anti-inflammatory drugs can be an alternative treatment strategy to halt degeneration and address IVD-related pain. In the present study, the controlled release and biologic potency of celecoxib, a selective COX-2 inhibitor,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
51
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(56 citation statements)
references
References 50 publications
4
51
0
1
Order By: Relevance
“…Certainly, this system fails to reproduce complex immunologic interactions. However, intradiscal injection of Etanercept in patients already demonstrated beneficial effects which were partially reproducible in our bioreactor system (Tellegen et al, 2018).…”
Section: Strengths and Limitationsmentioning
confidence: 59%
“…Certainly, this system fails to reproduce complex immunologic interactions. However, intradiscal injection of Etanercept in patients already demonstrated beneficial effects which were partially reproducible in our bioreactor system (Tellegen et al, 2018).…”
Section: Strengths and Limitationsmentioning
confidence: 59%
“…Power analysis was done to detect differences between TAA as bolus and TAA released by MSs. Our previous results demonstrated that an n of 6 allows for detection of differences in synovial inflammation, cartilage degeneration, and bone changes of given intervention (Tellegen et al, ). However, in treatment groups “MS‐TAA 1.0 mg” and “MS‐TAA 1.6 mg,” one rat was killed before the end of the study, leading to a reduction in n value of 5.…”
Section: Methodsmentioning
confidence: 99%
“…In a classcial pre-clinical study a controlled release system for the COX-2 inhibitor celecoxib (cyclooxygenase-2) was tested in a dog model for IVDD (Tellegen et al, 2018). Since celecoxib prevented IVDD progression and reduced inflammation, follow-up studes will be conducted in a clincal study aiming to eliviate the chronic pain associated with low back pain.…”
Section: Intervertebral Disc Degenerationmentioning
confidence: 99%
“…There are several research groups which have a track record of developing preclinical large animal models, some of which have managed to translate their research into clinical applications ( Kang et al, 2010 , 2013 ; Mcilwraith et al, 2011 , 2012 ; Godwin et al, 2012 ; Smith et al, 2013 ; Bach et al, 2017 ; Whitehouse et al, 2017 ; Goldberg et al, 2018 ; Tellegen et al, 2018 ; Broeckx et al, 2019 ; Tellegen et al, 2019 ). This − by no means exhaustive − list clearly demonstrates the collective efforts of the veterinary community to provide large animal models to be used in translational projects.…”
Section: Introductionmentioning
confidence: 99%